A lie someone told you about yourself - Davies, Peter Ho, 1966- (Houghton Mifflin Harcourt, 2021)
"A heartbreaking, soul-baring novel about the repercussions of choice, from the award-winning author of The Welsh Girl and The Fortunes"--